Avaliação do perfil, mortalidade e sobrevida dos homens com câncer de próstata atendidos em um serviço de referência do Espírito Santo - Zacchi, Sérgio Riguete (2012)
Introduction: Prostate cancer is the malignant neoplasm with the highest incidence in the Brazilian population and the second leading cause of cancer mortality among men, with an increasing trend over time and with 75% of cases occurring in men above 65 years old. Objectives: To assess the association of sociodemographic and clinical variables with the initial clinical staging; analyze mortality and survival and their associations with demographic and clinical variables in patients with prostate cancer. Methods: We analyzed retrospectively the data of men with prostate cancer registered in the Hospital Cancer Registry of the Santa Rita de Cássia Hospital (HSRC), in the city of Vitória, ES, Brazil during the period from January 1st, 2000 to December 31th, 2006. Data from the Mortality Information System(SIM) were used to determine the outcome. The data were analyzed using the Statistical Package for Social Sciences (SPSS) version 18.0. For the study variables that showed statistical significance, we calculated the crude and adjusted odds ratio using a multivariate logistic regression model. For estimating the survival, it was used the Kaplan-Meier method. For comparing survival curves, it was used the Log Rank test, with a significance level of 5%. The influence of the variables was calculated by Cox s multiple regression. Results: Of the 1290 men with prostate cancer, 758 (58.8%) were found alive, 308 (23.9%) had died of prostate cancer and for 224 (17.4%) the outcome was death by other causes. It was found a higher risk of being diagnosed with late stage men with PSA > 20ng/dl and Gleason score ≥ 7. The risk was reduced in those who reached the HSRC already diagnosed and without previous treatment. Death from prostate cancer was associated to a Gleason score > 9, PSA levels >20 ng/dl and the presence of metastasis. Death from other causes was associated to being a widower, entering the HSRC undiagnosed and untreated and with PSA levels > 50 ng/dl. It was found that Prostate Cancer Specific Survival (PCSS) at 5 and 8 years was 81.9% and 77.2% for all stages, and Overall Survival (OS) at 5 and 8 years was 70.1% and 69 8%, respectively. The variables Gleason score ≥ to 7, PSA >20 ng/dl and presence of metastasis were associated with a shorter survival. Conclusion: The variables that were associated with late clinical stage, mortality from prostate cancer and reduction of survival time are likely to be recognized and early diagnosed in screening consultations. It is extremely important to adopt actions from more effective health policies aimed at men with the goal of ensuring equal access to all those diagnosed with prostate cancer, so they can receive early diagnosis and timely treatment.